Performance Analysis of Micro, Small, and Medium Enterprises (MSMEs) of Ikola Coffee Using the Balanced Scorecard Method - Fahrul Rozi Maulana; M. Mustopa Romdhon; Reswita Reswita (Journal of Global Sustainable Agriculture, 2022)
MSMEs are one of several business sectors in Indonesia that have an essential role in increasing economic value and reducing unemployment. Bengkulu City is one of the cities in Indonesia that also takes advantage of the vital role of MSMEs. IKOLA Coffee is one of several MSMEs with its address at Jalan Musi No. 3 Padang Harapan Village, Gading Cempaka District, Bengkulu City, which was established on August 1, 2016, or has been established for six years. The purpose of this study was to determine the performance of MSME Kopi IKOLA, located in Gading Cempaka District, Bengkulu City, using the Balanced Scorecard method based on four perspectives, namely financial, customer, internal business processes, and growth and learning perspectives. The respondents in this study were IKOLA Coffee MSME customers who were 16 years old and had shopped at least once employees and business owners of IKOLA Coffee. The results of this study indicate that the business performance of MSME Kopi IKOLA is based on a financial perspective with a total score of 7, a customer perspective with a total score of 1, an internal business process perspective with a total score of 1, and a learning and growth perspective with a score of 2. Overall the company's performance value obtained is 0.73. Based on the rating scale, the business performance of IKOLA Coffee SMEs is included in the excellent category.